Cheating Prevention in E-proctoring Systems Using Secure Exam Browsers: A Case Study - Hussein Mahmood Mohammed; Qutaiba Ibrahem Ali (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
In this research, a case study has been conducted to analyze the possibility of preventing cheating or reducing it by using one of the lockdown browsers during the exam. An e-exam has been created using Moodle platform, and the exam has been conducted with the Safe Exam Browser (SEB) as a restriction program at one time and without it at another time, and an analysis has been made of the extent of the possibility of cheating during the exam for both cases. Wireshark and Registry Changes View programs have been used to observe the possibility of opening programs and applications or the ability of the examinee to use Windows tools during the exam. The use of Wireshark and Registry Changes View software showed high effectiveness in analyzing the examinee's device data and identifying the examinee's activity during the electronic exam, to give a clear perception of the possibility of preventing access to resources and applications on the examinee's device. The researchers concluded that the use of lockdown browsers is very necessary to prevent the examinee from accessing the resources on his device, which leads to a significant reduction in cheating during the electronic exam. The research contributions are two, the first one is the use of analyzing programs to observe the examinee`s activity during the exam, and the second one is presenting the lockdown browsers` features.